Bio‑graphies. De la figure paternelle à la pratique scripturale dans La place d’Annie Ernaux - Rachwalska von Rejchwald, Jolanta (Romanica Silesiana)
Over the years Annie Ernaux has been trying to deal with the theme of her father’s death. And yet she could not find the appropriate form to express a specific distance that emerged at some point when her father was still alive. By experimenting with various novel literary forms she came to a realization that only the departure from fiction would allow her to convey a kind of “truth” about her father and this unique distance (supposedly attributable to her leaving the social class she had been born and raised in). Consequently, Ernaux decides to reject “literature” and to write an autobiographical piece in the first person, which is somehow flat because it is stripped of all rhetoric layers. In this article I endeavour to show that a deeply engraved thirst for telling the truth about one’s father simultaneously becomes a story about one’s ambitions and about seeking one’s identity. Primarily, however, A Man’s Place is a story about searching for one’s own form of expression and growing up to writing.